ANALISIS KONSISTENSI MATRIKS KEPUTUSAN : SUATU PERBANDINGAN NUMERIK - Farikhin Farikhin (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
In this paper, we study some algorithms to improve consistency of resiprocal pairwise matrix. The algorithm is proposed by using relationship with multiplicative preference relation and fuzzy preference relation. An example is presented to evaluate these algorithms.